Parental Role Modelling as a Determinant of Entrepreneurial Decision-making: Case from Saudi Arabia - Aldhehayan, Abdulaziz (مجلة العلوم الإدارية و الإقتصادية, 2025)
Drawing on theoretical frameworks such as entrepreneurial orientation (EO), social learning theory (SLT), role modelling, and family embeddedness. Based on the developed framework, this research examines the parental role modelling and family embeddedness in shaping their offspring's decision to open a new venture. Logistic regression (Logit) was employed to evaluate the study hypothesis, utilising data collected from a sample of 638 individual adults from in the Kingdom of Saudi Arabia (KSA). The findings, which were obtained by STATA 19 software, provide evidence that having self-employed parents serves as an important role model, confirming the influence of parental role modelling as an important predictor of entrepreneurship.